The role of food as part of person-centred palliative care: An exploratory ethnographic study - Victoria Wicks; Sarisha Philip; Montana Warbrick; Wenshan Li; Khajadour Bandk; Alexandria Hector; Danielle Caissie; Peter Lawlor; Jennifer Yeung; Krystal Kehoe MacLeod (Palliative Care and Social Practice)
Background: Palliative care is about more than providing high-quality medical care; it is about maximizing quality of life while dying. The role that food plays in palliative care is not well studied or understood. Most research on food in palliative care focuses on nutrition, rather than the importance of serving food that patients recognize, enjoy, and want to consume. This study aimed to understand the role of food as an integral part of person-centred palliative care. Methods: We engaged with patients, caregivers, staff, and hospital decision-makers at the Bruyère Health Palliative Care Unit in Ottawa, Canada. We focused discussions on the role and importance of food as part of palliative care, gaps regarding food in this setting, and how their needs could be better met. To collect data, we used rapid team-based ethnography, including 10 days of fieldwork in the Palliative Care Unit, informal conversations with patients, caregivers, and staff, observations of meals, and content analysis of food-related documents. Methods also included arts-based drawing techniques, semi-structured interviews with patients ( n  = 4), caregivers ( n  = 3), and hospital administrators and food services decision-makers ( n  = 4), and self-reflexive journal entries by researchers. Data from all sources were triangulated, and Reflexive Thematic Analysis was used to inductively identify key themes. Results: The three overarching themes we found were: (1) the role of food changes for patients and caregivers as they progress through their palliative care journey, (2) there is a disconnect between the food services department and palliative care unit staff and patients, and (3) there is a need to have difficult conversations around the changing role of food with patients and caregivers and staff do not feel well-equipped to do this. Conclusion: To improve care, we first recommend addressing communication gaps by equipping palliative care providers with the skills they need to have difficult conversations about food. Secondly, we recommend that providers work closely with the food services department to ensure that they are aware of the unique needs of palliative care patients and help them identify areas where addressing unmet needs is aligned with quality improvement initiatives to accelerate change for patients and caregivers.